IMPROVING STUDENTS ENGAGEMENT IN READING CLASS BY USING STUDENT TEAMS-ACHIEVEMENT DIVISION (STAD) - Huda, Nur (English Language Education Study Program, 2020)
This research is a classroom action research. It is aimed to describe how Student Teams-Achievement Division (STAD) improves the students engagement in reading comprehension activities. The problems found in this research were the ninth grade students of MTs Negeri 4 Sambas were low engaged in reading comprehension activities. This research was conducted in class B. The procedure of the research consisted of planning, enacting, observing, and reflecting. In this study, the researcher was the teacher of the research subject who implemented STAD in teaching reading comprehension. The data were in form of quantitative and qualitative data. The tools of data collection were observation checklist, field note, ad questionnaire. The quantitative data were collected from the observation checklist, and questionnaire. The quantitative data were analyzed by statistic formula. The qualitative data were analyzed by using a method stated by Best and Kahn (2006). From the result of the research, the researcher found that STAD can improve the students engagement in reading class. They were enthusiastic to participate in class presentation and discussion. During the learning process, they were active to learn better such as trying to understand the reading texts by asking questions and sharing their knowledge and ideas to other students.